Gambaran Profil Hematologi pada Pasien Preeklampsia dan Kehamilan Normotensi di RSIA Abby - Tanjung, Rizky Ananda; Zubir; Albin, Iskandar (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2025)
Preeclampsia is hypertension that occurs after 20 weeks of gestation accompanied by proteinuria. Decreased function of a number of organs and systems in patients with preeclampsia causes various changes in pregnancy, one of which is a change in the hematological profile of pregnant women. This study aims to describe the hematological profile in patients with preeclampsia and normotensive pregnancy at RSIA Abby for the period August 2021-August 2022. The research method is a quantitative descriptive with a cross-sectional approach. The sampling technique in this study used a simple random sampling technique with a total sample of 142 samples. The results of this study were preeclampsia patients aged 20-35 years (57.7%), multigravida (84.5%). Normotensive pregnancy aged 20-35 years (76.1%), multigravida (74.6%). The majority of patients with preeclampsia have erythrocyte, hemoglobin, hematocrit, MCV, MCH, MCHC, and leukocyte and platelet counts within normal limits. The majority of normotensive pregnancy patients have normal ranges of erythrocytes, hematocrit, MCV, MCHC, leukocytes, and platelets, while hemoglobin and MCH levels are decreased. So the conclusion of this study is that all hematological profiles in preeclamptic patients are within normal limits while in normotensive pregnancies there is a decrease in hemoglobin and MCH levels.